Teaching Islam in the Palembang Malay During the Dutch Colonial Era - Dayun Riyadi; Ahmad Suradi; Qolbi Khoiri; Siti Marpuah (Jurnal Sejarah Citra Lekha)
This paper examines the impact of Dutch colonial policies on Islamic education in Palembang during the colonial period. Under Dutch rule, strict regulations were enforced on Islamic education, primarily aimed at controlling religious teachers and preventing them from using educational institutions to foster anti-colonial sentiment. The colonial government sought to weaken local resistance, often targeting influential ulama who played a key role in the dissemination of Islamic knowledge. In Palembang, traditional Islamic education was the dominant system during the Sultanate period, but with the rise of Dutch colonial power, Islamic education became marginalized, with a particular emphasis on the role of ulama and traditional Islamic teaching. Over time, the local society began to recognize the need for Dutch-style education, driven by the promise of better job opportunities for those holding Dutch school diplomas. Despite the establishment of Dutch-run schools, educational standards in Palembang remained low compared to other regions of Indonesia. This was due to both the limited public awareness of the importance of education and the inability of the colonial government to fulfill the educational aspirations of the local population. The paper highlights the complex interplay between colonial educational policies, local traditions, and the changing perceptions of education in Palembang during the colonial era.